الشيخ محمد مردوخ الكوردستاني حياته وآثاره العلمية (عرض وتحليل) - جلال, أ.د.اسماعيل محمد; أحمد, نورى محمد زاهد (Sulaimani Journal for Humanities, 2023)
This research deals with an show a prominent figure in Iranian Kurdistan, Sheikh Mardukh, who is called Jamal al-Din, and who is known as Ayatollah is one of the sheikhs of Mardukhiyyah, and he is an imam and Juma'ah speaker in Sanandaj, in the Dar al-Ihsan Mosque, the research also shows that this series serves religious science and higher literature, and he has an active role in the religious and social events and issues in Iranian Kurdistan, with a high quality attitudes, fine manners, visiting relatives, respecting the guest, honesty, trustworthiness, loyalty and courage, and preserving the time until the last day of his life.